Sistema de metas de inflação no Brasil e a controvérsia sobre o investimento agregado - Araújo, Isadora (2021)
This essay has as its goal to verify the implications of brazilian monetary policy, starting from the base interest rate over the aggregated investment. The research considered the period beggining from the adoption of the inflation target in Brazil up to the year of 2019. Firstly, the main theoric aspects that contribuited to the emergence of the inflation target in the macroeconomic literature are consolidated, which are centralized in the Phillips curve analysis and in the debate about the neutrality of the coin. After that, the research went to the verification of the general objective, making use of a quantitative analysis over the brazilian monetary policy, inside the context of the inflation target and its implications to the results of aggregated investment. This investigation has concluded that, once chasing the inflation target, the monetary authorities, using the interest rate as its main instrument, may generate deleterious effects over the aggregated investment. However, this investigation was not conclusive from the opposite point of view, in other words, if there are downwards variations in the base rate, it is not concluded what happens with the aggregated investment. Lastly the qualitative analysis was complemented by an empiric verification made from time series data, that, in the light of evidences obtained through cointegration tests and through the Granger Causality Test, was conducted to a modeling of simultaneous equations with error correcting mechanisms. This investigation stated that, making use of the base fee, the monetary policy has no meaningful impact over the aggregated investment, neither when the Selic goes up, or when it goes down